PERAN ARTIFICIAL INTELLIGENCE DALAM MANAJEMEN SUMBER DAYA MANUSIA (SDM) PADA LEMBAGA PENDIDIKAN ISLAM DI ERA REVOLUSI INDUSTRI 5.0 - Nur Indra Damayanti; Ririn Inayatul Mahfudloh (Walada: Journal of Primary Education, 2026)
This study aims to determine the planning and implementation of Artificial Intelligence (AI)-based human resource management at SMK Wahid Hasyim Glagah Lamongan. This research uses a qualitative approach with a descriptive research type. Data were collected through interviews, observations, and documentation. The data analysis techniques used were data reduction, data presentation, and conclusion. The results of the study indicate that the use of digital technology and Artificial Intelligence has begun to be implemented in managing human resources within the school environment. In the planning stage, AI technology is utilized by teachers to assist in preparing learning tools such as teaching materials, searching for learning references, and creating evaluation instruments. In addition, digital systems also support school administrative management, including student data processing and cloud-based document storage. In the implementation stage, the use of AI can be seen through various digital applications that support both learning and administrative activities. Teachers use AI technology to develop teaching materials and design more innovative learning strategies, while administrative staff utilize digital systems to manage school administrative data more systematically and efficiently. Therefore, the use of Artificial Intelligence in human resource management at SMK Wahid Hasyim Glagah Lamongan can improve the effectiveness, efficiency, and productivity of teachers and educational staff, while also supporting the improvement of learning quality in the era of the Industrial Revolution 5.0